A COMPARATIVE RANDOMISED CONTROLLED PARALLEL GROUP STUDY OF EFFICACY AND TOLERABILITY OF LABETALOL VERSUS METHYLDOPA IN THE TREATMENT OF NEW ONSET HYPERTENSION DURING PREGNANCY - VERMA, REENA; LAHON, KINGSHUK; TONPAY, SD; JOSHI KALE, VRUNDA; JAIN, DK (International Journal of Life Science and Pharma Research, 2012)
Hypertensive disorders in pregnancy remain one of the major causes of maternal and perinatal mortality in developing as well as developed countries and can result in hospital admission, pre-eclampsia and possible premature delivery. Antihypertensive drugs are often used to lower blood pressure to prevent this progression to adverse outcomes for the mother and the fetus. Methyldopa has often been used as control while comparing the effects of different dugs. Labetalol has also been successfully used for treatment of hypertensive disorders in pregnancy. Hence, we wanted to compare the efficacy and tolerability of labetalol versus methyldopa in pregnancy induced hypertension (PIH) in an Indian population. We carried out a prospective randomised controlled parallel group study on 90 outpatients as well as inpatients of the antenatal ward of Obstetrics and Gynaecology department of our tertiary care teaching hospital. Pregnant patients (20-40 weeks gestational age) newly diagnosed with blood pressure of ≥140/90mmHg and single ton with vertex presentation were included in the study. All patients with a history of hypertension, diabetes, Rh iso-immunisation, depression, congestive heart failure, heart block or bronchial asthma, patients at risk of major obstetric complications - antepartum haemorrhage, malnutrition, twins and hydramnios during the current pregnancy and patients who had already received antihypertensive drugs were excluded. 45 patients each were randomised to either of the two treatment arms – oral methyldopa or oral/IV labetalol. Difference in BP measurements pre- and post-treatments (on 8th day) were analysed by applying paired‘t’ test for the difference in pre- and post-treatment values. For inter group analysis, we applied chi-square test, using Epi Info statistical software version 3.3. A P-value < 0.05 was regarded as significant with 95% confidence limits. Adverse events were documented and subjected to causality analysis by Naranjo’s scale. There was no statistically significant difference in antihypertensive efficacy between the methyldopa and labetalol groups. Adverse drug reactions were possible to probable and occurred less with labetalol. However, despite equal efficacy and better tolerability, effect on fetal and maternal outcomes determines whether labetalol is better than methyldopa in PIH.